Pancasila Di Wilayah Syariat Islam: Kajian Pemahaman Nilai-Nilai Pancasila Dan Landasan Sikap Toleransi Masyarakat Pedesaan Di Aceh Barat - Triyanto; Yeni Sri Lestari (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2019)
Recently, many anti-pancasila cases have appeared in the mass media, both in print and in electronic form. The place is not only the village community, but also the city people who actually have the character of a plural society, are aware of the differences and even have an individualistic attitude. In rural communities, it usually holds the values of togetherness, mutual love and upbringing and respect-respect and respects each other. In fact, a slight difference can lead to a case of intolerance. This study aims to determine how the views and attitudes of rural communities in West Aceh, an area that enforces Islamic law against the values of Pancasila. It also aims to find out how the loyalty of rural communities in West Aceh to the ideology of Pancasila. This research uses a qualitative method. The informant is determined by purposive sampling, that is selecting the community as an informant according to the expertise, and the mentioned expertise is meant to understand the problem that becomes the subject of this study. The results show that Pancasila is only known by the older generation and this generation understands that the values of Pancasila run as a tolerance setting, so that citizens do not discriminate against the existence of people outside of Aceh, let alone outside the region. This generation also understands that the implementation of Islamic law is a loyalty to the ideology of Pancasila because the first principle is expressed as faith in the Mahaesa. So there is no contradiction between the Islamic Shari'a and Pancasila. Unfortunately, the younger generation does not understand how Pancasila is. This generation has never received socialization about Pancasila and only knows about the flag ceremony, which often reads the Pancasila text. The researcher's interpretation is that after the 1998 Reformation, the community did not experience the socialization of Pancasila values. Unfortunately, some understand that Pancasila and the Islamic Sharia'ah are contradictory. In this narrow sense, it can threaten the existence of Pancasila. But by and large, the contradiction is limited because of the religious differences that can still be harmonized values of unity.